Proteins from insects: A sustainable alternative for oral health within the one health concept and the planetary health diet - Marta Mazur; Maciej Jedliński; Irena Duś-Ilnicka; Artnora Ndokaj; Florence Carrouel; Livia Ottolenghi; Denis Bourgeois (Human Nutrition & Metabolism)
The growing use of insect-derived proteins as a food source, driven by their nutritional benefits and low environmental impact, raises questions about their impact on human health, particularly oral health. This position paper analyzes the potential implications of integrating insect proteins into the diet, with a special focus on dental, periodontal, and oral microbiome health. By offering complete amino acid profiles, omega-3 fatty acids, and antimicrobial peptides, insect proteins may help address nutritional gaps and positively influence oral tissue regeneration and microbiome balance. Their low-carbohydrate content also reduces substrate availability for cariogenic bacteria, making them a valuable alternative to starch- or sugar-rich diets. We justify this dietary transition in light of present nutritional deficiencies and demonstrate how insect proteins can register within a holistic approach to global health (One Health) and the Planetary Health Diet, supporting sustainability and improving overall health. However, further studies are needed to evaluate their safety as potential sources of allergens and contaminants. Both in-vitro and in-vivo studies are needed to assess correlations with the oral microbiota and its most frequent dysbiosis-related manifestations.